Keywords and keywording. Issue 6 (2nd November 2022) - Highmore, Ben
ABSTRACT: This article pursues two tasks. The first is to clarify the value and productivity of Williams's Keywords: a vocabulary of culture and society (first edition 1976, second expanded edition 1983a) for the project of Cultural Studies. This clarification is helped, I argue, by reading it alongside Vološinov's Marxism and the philosophy of language (published in Russian in 1929, translated into English in 1973). The second and related task is a speculative development of 'keywording' (or keyword analysis) based on an assessment of the limitations and potential of Williams's broad philological project for today. My argument is that Keywords initially sought to provide a historical map of changing patterns of feeling associated (primarily) with industrialization in England, and that this was sometimes in an uneasy relationship with what he would later name as the project of providing 'resources of hope'. One consequential limitation of the original work is that its historical perspective was built on semantic examples provided by the OED (or to give it its original title, the Oxford new English dictionary on historical principles ) and supplemented with Williams's literary studies. My suggestion is that Cultural Studies can develop (and has, to some degree, already developed) Williams's Keywords project without it being centred on literature or beholden to the OED . This would mean treating the project less as an exemplary milestone or methodology and more as an unfinished and unfinishable project whose methodology is critically dynamic: in other words, to move from Keywords to 'keywording' requires altering Williams's methodology. In conclusion I speculate about the ways in which the historical aims of keywording could be expanded to make it more conducive to providing 'useable histories' and semantic counter-narratives, while also pursuing the radical contextualism of Vološinov and Bakhtin.